Brunei And Aceh: A Manuscript-Based Study of Cultural And Historical Relationship - NFN, Fakhriati (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2018)
Dari sisi letak geografis, Brunei dan Aceh adalah dua suku bangsa yang berada di posisi berjauhan, pulau Kalimantan dan Sumatera. Namun, keduanya memiliki banyak kemiripan antara satu sama lainnya. Keduanya berada dalam satu rumpun Melayu, budaya, dan karakter yang mirip. Dari sisi sejarah, kedua suku ini memiliki hubungan baik, baik pada tatanan kesultanan maupun pada level rakyatnya. A. Hasyimi mengatakan bahwa qanun yang dipakai di Brunei adalah hasil adopsi dari qanun yang ada di Aceh. Selain itu kemiripan dari sisi budaya adalah, seperti permainan rakyat, cara masuk rumah baru, dan tepung tawari. Kemiripan-kemiripan ini menjadi menarik dikaji lebih jauh tentang hubungan sejarah Brunei dan Aceh. Tulisan ini bertujuan untuk menggali hubungan sejarah antara kesultanan Brunei dan Aceh, termasuk hubungan yang baik antara ulama dalam menyebarkan ajaran Islam. Penelitian ini didasarkan pada temuan-temuan terutama yang terdapat dalam manuskrip Aceh dan Brunei. Kajian ini mengunakan pendekatan filologis dan antropologis untuk mengungkap informasi relasi antar kedua etnis ini. Diharapkan hasil kajian ini dapat menjadi pendukung pelestarian warisan yang dimiliki kedua suku bangsa Brunei dan Aceh, terutama terkait manuskrip dan bukti sejarah tentang hubungan kedua suku bangsa tersebut. Kata Kunci: Aceh, Brunei, manuskrip, sejarah, budaya, dan MelayuGeographically, Brunei and Aceh are separated by the ocean. One is located on the island of Kalimantan and the other on the island of Sumatra. Despite the distance, these two entities possess many similarities. Their people are of Malay origin, alike in culture and character. Historically, the relationship between them, be it at the level of sultans or subjects, is as well as it can be. For example, A. Hasyimi stated that Brunei adopted qanun (law) from Aceh. Other similarities can be found in their culture, such as folk games, housewarming celebration, and flour ritual. These similarities invite a deeper examination into the relationship between Brunei and Aceh. This study aimed to investigate the connection between the Brunei and Aceh sultanates, as well as the relationship between their ulama in spreading Islam. Using historical manuscripts from both places as primary sources, this study employed philological and anthropological approaches to achieve its objectives. It is hoped that the result of this study could be used to support the heritage preservation of Brunei and Aceh, especially in terms of historical manuscripts which have successfully proved their close relationship.Keywods: Aceh, Brunei, Malay, manuscript, history, culture